2019
DOI: 10.1186/s12951-019-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of biocompatible bovine serum albumin nanoparticles composed of nano graphene oxide and AIEgen for dual-mode phototherapy bacteriostatic and bacterial tracking

Abstract: Background Efficient and highly controllable antibacterial effect, as well as good biocompatibility are required for antibacterial materials to overcome multi-drug resistance in bacteria. Herein, nano graphene oxide (NGO)-based near-infrared (NIR) photothermal antibacterial materials was schemed to complex with biocompatible bovine serum albumin (BSA) and aggregation-induced emission fluorogen (AIEgen) with daylight-stimulated ROS-producing property for dual-mode phototherapy in the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…23a). 280 Due to its strong hydrophobicity, the AIE PS could be facilely entrapped into amphiphilic nano-graphene oxide and BSA. The integration of biocompatible BSA was schemed to improve the water solubility and physiological stability of the nanocomposite.…”
Section: Combining With Other Photothermal Conversion Agentsmentioning
confidence: 99%
“…23a). 280 Due to its strong hydrophobicity, the AIE PS could be facilely entrapped into amphiphilic nano-graphene oxide and BSA. The integration of biocompatible BSA was schemed to improve the water solubility and physiological stability of the nanocomposite.…”
Section: Combining With Other Photothermal Conversion Agentsmentioning
confidence: 99%
“…This allowed them to use low concentration of GO, which in turn showed lesser human dermal fibroblasts but retained its antibacterial activity. Zhang et al reported a biocompatible NGO-BSA-AIE nanoparticle to show superior antibacterial effect via ROS generation along with fluorescent bio-tracking of the bacterial activity . AIE produces fluorescence under white light of 10 mW/cm 2 and conjugation with BSA via hydrophobic interactions ensures its stability in aqueous solutions.…”
Section: Graphene-based Photoinduced Antibacterial Applicationsmentioning
confidence: 99%
“…Zhang et al reported a biocompatible NGO-BSA-AIE nanoparticle to show superior antibacterial effect via ROS generation along with fluorescent bio-tracking of the bacterial activity. 69 AIE produces fluorescence under white light of 10 mW/cm 2 and conjugation with BSA via hydrophobic interactions ensures its stability in aqueous solutions. Irradiation with 795 nm laser at 2.5 W/cm 2 for 5 min and daylight for 1 h resulted in dual-mode phototherapy.…”
Section: Graphene-based Photoinducedmentioning
confidence: 99%
“…In addition, the existence of molecular rotors in the AIEgen skeleton could facilitate excited-state energy dissipation via non-radiative decay and thus promote photothermal conversion [ 37 , 38 ]. Combining these unique features, a few AIEgens were developed for synergistic photodynamic and photothermal treatment by making full use of both ROS and heat [ [39] , [40] , [41] ]. However, those researches mostly focused on the bacteria killing in solution or infection treatment in vivo, researches regarding the fabrication of AIEgen-loaded hybrid material as antimicrobial surfaces are still rare.…”
Section: Introductionmentioning
confidence: 99%